Mediating scarcity in pandemic times: an ethnographic study on the prevention and control of SARS-CoV-2 infections during the emergence of the corona crisis in the Netherlands - Jenske Bal; Bert de Graaff; Margreet C. Vos; Roland Bal (BMC, 2022)
Abstract Background In this paper we explore how staff involved with infection prevention managed the emerging COVID-19 crisis in the context of scarcity of Personal Protective Equipment (PPE), focussing specifically on the (re)writing of guidelines. We conceptualize guidelines as 'mediating devices' as they translate between evidence and clinical practice, between management and the workplace, as well as the different values embedded in these domains. It is this mediation, we argue, that adds to the resilience of healthcare organizations. The setting for this research is an elite academic hospital in the Netherlands during the emergence of the COVID-19 pandemic. Methods We conducted non-participative observations, semi-structured interviews, and document analysis during the emerging pandemic (March-July 2020). We observed meetings from the crisis team and the unit for infection prevention (210 hours), interviewed members of these teams (21 interviews) and analysed guidelines and flowcharts concerning infection prevention, as such collecting a unique and rich qualitative dataset. Analysis was done through thematic coding. Results Our results show the writing and rewriting of guidelines as a fundamental characteristic of dealing with scarcity and adding to resilience. We found three main practices our research participants engage in while trying to manage the uncertain situations emerging from the scarcity of personal protection equipment. The first practice we observe is defining safety; dealing with different perspectives and experiences of what 'working safely' means. The second entails the anticipation of scarcity by which our participants aim to control the situation through monitoring, research and creating scenarios. The third practice we observe is finding new ways to use PPE that is available, by experimenting and tinkering with the material. Conclusion Infection prevention guidelines are crucial in managing the emerging crisis. We discuss how the writing of guidelines mediates between different settings, timeframes, and different worlds of quality. Through (re)writing there is a constant negotiation and discussion with the various actors about what works, and there is a continuous adaptive attitude. At the cost of a lot of work and struggle, this creates a resilient and inclusive work environment useful in a long-lasting crisis.